A Mapping Review to Understand Web and Mobile Apps Accessibility for Adults with Autism - Ribeiro, Danilo Monteiro; Azul, Celeste; Negromonte, Vitor; Melo, Felipe Vasconcelos; Matias, Gabriel Walisson; Farias, Adna; Chaves, Ana Paula; Gama, Kiev (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2025: Anais do XXI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2025.246487, 2025)
Context: With the rise of the neurodiversity topic, there is a need to investigate the demands of autistic individuals for Information Systems, ensuring a more accessible and user-friendly experience. Problem: Despite existing guidelines for autistic individuals, there is a limited synthesis of findings to identify gaps and best practices, particularly for adults. Solution: This article reviews key guides, frameworks, evaluation tools, recommendations, and design standards that support the development and usability assessment of mobile and web applications for autistic users. Method: This research follows a mapping study approach with a narrative synthesis of 23 research articles. IS theory: This study applies Cognitive Load Theory to analyze usability challenges and evaluate the effectiveness of accessibility guidelines. Results: 23 papers were found within the Guideline for the Accessibility of Web Interfaces with a Focus on Autism (GAIA), covering visual/textual vocabulary, customization, redundant representations, participation, multimedia, and navigability. However, no studies were found in state visibility, recognition, predictability, response to actions, and touchscreen interactions. Barriers were analyzed across cognitive overload, processing, distinguishability, and breaking expectations.Contributions in the Field: We identified nine frameworks for designing and evaluating Information Systems for autistic users, improving usability and accessibility. However, further investigation is needed to assess the effectiveness of these guidelines, as some remain unvalidated.